Cognitive Construction of Critical Thinking in Argumentative Writing among Arabic Language Education Students at UIN Fatmawati Sukarno Bengkulu: البناء المعرفي للتفكير الناقد في الكتابة الحجاجية لدى طلبة قسم تعليم اللغة العربية بجامعة فاطماواتي سوكارنو الإسلامية الحكومية بنجكولو - Achmad Ja'far Sodik; Wildana Wargadinata; Abdul Wahab Rosyidi; Ahmad Nuruddin (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to reveal the cognitive construction of critical thinking in the argumentative writing of students in the Arabic Language Education Department (PBA) at UIN Fatmawati Sukarno Bengkulu. Using a qualitative approach, the data consisted of units of ideas within sentences, paragraphs, and texts derived from students’ argumentative essays collected through writing assignments in the insya’ course. Data analysis followed Miles and Huberman’s model: data reduction, data display, verification, and conclusion drawing. The findings show that the cognitive construction of critical thinking comprises four dimensions: interpretation, analysis, inference, and evaluation. Interpretation involves perspective and definition formation; analysis includes argument components and structure; inference consists of deductive and inductive reasoning; and evaluation covers argument accuracy and logical validity. These findings contribute to the development of argumentative writing instruction by mapping how critical thinking emerges in students’ texts.